ENHANCEMENT OF MECHANISMS OF COORDINATION OF THE BUDGET POLICY IN EUROPEAN UNION - D. Bolotin (Вестник университета, 2016)
In modern conditions of development of economy of the European Union (EU) stabilization of the budget relations is one of the most important aspect of development of the financial sphere of this integration group. In the article the main mechanisms of coordination in the budget sphere and the prospects of its development in the conditions of expansion of the EU are considered.